Observasi Dampak Cemaran Lingkungan Yang Di Sebabkan Oleh Limbah Pasar Di Kecamatan Medan Denai Dan Medan Tembung - Maria Sianipar; Sri Muthia Hasan; Yogi Turnip; Dhio Lubis; Meilinda Suriani Harefa; Syukri Hidayat (Fakultas Teknik Universitas Cenderawasih, 2023)
Findings in the Medan Denai and Medan Tembung traditional markets show that waste management is good, but waste management discipline has not been implemented, especially in the Sukaramai, Mandala, Pagi and Sore traditional markets, it appears that there are still people who do not implement it. don't care about cleanliness unless it's clean.Research in traditional markets shows that waste management is still not adhered to, such as a lack of waste sorting and processing processes, as well as market environments filled with large amounts of waste. One of the problems with waste in traditional markets is that there is a relatively large amount of it, which creates its own problems.This happens in traditional markets as an economic medium, where existing activities such as buying and selling from traders to consumers or from traders to traders indirectly create piles of rubbish.Studies at traditional markets in Medan City show that the behavior of traders in disposing of waste has a significant impact on increasing the volume of waste in traditional markets.In this case, handling waste problems in traditional markets actually requires the participation of traders.The waste problem at Sukaramai Market, Mandala Market, Morning Market and Afternoon Market is caused by an inefficient management system, accumulation of unsorted waste and the absence of a special group appointed by market managers to handle cleanliness and waste problems. Lots of rubbish scattered in the market.